Dampak Sistem Pembayaran Qris Terhadap Omset Penjualan UMKM Di Surabaya - Lela, Aleksia; kusmayati, nindya kartika; Kurniawati, Yuli; Wulansari, Dhyah (Universitas Kadiri, 2023)
This research which aims to determine the impact of using the Qris payment system on MSME sales turnover in Surabaya. The research was aimed at UMKM merchants and consumers who use the Qris payment system in the city of Surabaya, with a population of 70 people from teenagers to adults. Of these 70 respondents, the authors also make it as a sample. The author chose the quantitative method in this study with the process of accumulating data by distributing questionnaires. The test uses simple linear regression, using instrument tests consisting of validity tests, reliability tests, heteroscedasticity tests, and also multicollinearity tests. Then proceed with the classical test which consists of a normality test, heteroscedasticity, and multicollinearity test. Based on the results of the t test, a simple linear regression equation is formed, namely Y = 13.985 + 0.726x, which means that the lack of use of the Qris payment system is fixed, so the effect on sales turnover also does not change. Likewise, if the use of the Qris payment system increases, the effect on sales turnover will also increase. The Qris payment system is highly recommended for consumers and MSMEs in Surabaya in the process of buying and selling transactions, as well as payments that are practical, easy, and guaranteed security.